Intralesional 3% sodium tetradecyl sulphate versus hot water in oral cavity hemangioma: a comparative study - Mishra, Sayambika; Acharya, Souvagini; Kar, Arunima; Mohanta, Fakir Mohan; Samal, Smruti Ranjan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Oral cavity lesions fall among the few most common presentations in the outpatient department of ENT. Hemangioma in oral cavity though do not usually account for any life threatening or serious condition but hampers day to day activities like chewing, speaking and occasionally bleeding from oral cavity. Timely diagnosis and treatment solves the above problem. Though there are various modalities of treatment ranging from cryosurgery to surgical ablation, sclerotherapy is an evolving, effective and easy method for reduction of the size of lesion and preventing recurrence. It can be done as a day care procedure. The aim was to compare between the efficacy of 3% sodium tetradecyl sulphate and hot water in oral cavity hemangiomas. Methods: A total of 20 patients presenting to the OPD, department of ENT, VIMSAR, Burla, with diagnosis of hemangioma in oral cavity between January 2018 to January 2019 were selected for the study. They were divided into two groups. Group A was administered 3% sodium tetradecyl sulphate whereas group B was administered hot water, both intralesionally, at multiple sites of lesion. Injection were repeated after an interval of 2 weeks for a period of 3-4 months. The results were routinely analysed clinically and statistically and the statistical significance was set at p<0.05. Results: There was a significant improvement (p<0.05) in most of the parameters measured, in group A patients as compared to group B patients. Conclusions: 3% sodium tetradecyl sulphate is a better sclerosing agent than hot water in cases of oral cavity hemangiomas.